The Glasgow alcoholic hepatitis score identifies patients who may benefit from corticosteroids. Issue 12 (12th July 2007) - Forrest, E H; Morris, A J; Stewart, S; Phillips, M; Oo, Y H; Fisher, N C; Haydon, G; O'Grady, J; Day, C P
Abstract : Introduction: There is no consensus on the pharmacological treatment of alcoholic hepatitis. The Glasgow alcoholic hepatitis score (GAHS) has been shown to be more accurate than the modified Maddrey's discriminant function (mDF) in the prediction of outcome from alcoholic hepatitis. This study aimed to determine whether the GAHS was able to identify those patients who would benefit from corticosteroids. Methods: 225 patients with an mDF greater than or equal to 32 from five hospital centres in the United Kingdom were reviewed. Patient survival relative to the GAHS and the use of corticosteroids was recorded. Results: 144 patients with an mDF greater than or equal to 32 (64%) also had a GAHS greater than or equal to 9. There was no difference in survival between untreated or corticosteroid-treated patients for those with a GAHS less than 9. For patients with a GAHS greater than or equal to 9 the 28-day survival for untreated and corticosteroid-treated patients was 52% and 78% (p = 0.002), and 84-day survival was 38% and 59% (p = 0.02), respectively. Conclusions: Among patients with an mDF greater than or equal to 32, there was no appreciable benefit from treatment with corticosteroids in patients with a GAHS less than 9. Patients with a GAHS greater than or equal to 9 have an extremely poor prognosis if they are not treated with corticosteroids, or if such treatment is contraindicated.